2017
DOI: 10.1016/j.ejogrb.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus oxytocin for prevention of post-partum haemorrhage at caesarean section in the United Kingdom: An economic impact analysis

Abstract: At list price, the introduction of carbetocin appears to provide improved clinical outcomes along with cost savings, though this is subject to uncertainty regarding the underlying data in efficacy, resource use, and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…In a simulated model of 1500 caesarean sections over a 12-month period, using clinical data from a meta-analysis and pricing data from the UK, carbetocin was found to have a 91.5% probability of being associated with a lower incidence of postpartum haemorrhage (reducing cases with blood loss > 500 ml from 88% to 58%) and savings of > £27,000 compared with oxytocin [78]. A similar study from Malaysia found an even higher clinical impact of carbetocin, with a prevention of 54 cases of postpartum haemorrhage and 52 transfusions per 1500 caesarean sections annually, when compared with oxytocin [79].…”
Section: Carbetocinmentioning
confidence: 99%
“…In a simulated model of 1500 caesarean sections over a 12-month period, using clinical data from a meta-analysis and pricing data from the UK, carbetocin was found to have a 91.5% probability of being associated with a lower incidence of postpartum haemorrhage (reducing cases with blood loss > 500 ml from 88% to 58%) and savings of > £27,000 compared with oxytocin [78]. A similar study from Malaysia found an even higher clinical impact of carbetocin, with a prevention of 54 cases of postpartum haemorrhage and 52 transfusions per 1500 caesarean sections annually, when compared with oxytocin [79].…”
Section: Carbetocinmentioning
confidence: 99%
“…14 Peru, 20 Senegal, 21 Tanzania, 22 Uganda, 23 and the UK. [24][25][26][27] One of the studies was an international study with a hypothetical cohort. 28 Eleven of these studies were conducted from 2011 to 2018 and four studies were conducted from 2007 to 2010.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…28 Eleven of these studies were conducted from 2011 to 2018 and four studies were conducted from 2007 to 2010. 14,17,18,22 Out of the 15 studies, three studies were funded by pharmaceutical companies, 16,20,27 Institute for Health Research, and others, 17,18,21,22,24,28 three studies were not funded, 23,25,26 in two studies (abstracts) it was unclear whether they were funded or not, 14,15 and one study did not disclose funding sources. 19 The relevant healthcare perspective was used in all studies except in one study, which adopted a WHO perspective.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations